“Nos qui cum eo fuimus”: representação e memória do milagre dos estigmas de Francisco de Assis nas hagiografias franciscanas “oficiais” e “não oficiais” (séculos XIII e XIV) - COSTA, Alex Silva (2023)
This Thesis analyzes the representation of the miracle of the stigmata of Francis of Assisi in the ―official‖ and ―unofficial‖ Franciscan hagiographies of the 13th and 14th centuries, among them, the Vita Prima (1C) and Vita Secunda (2C) of Thomas of Celano, the Legenda Maior (LM) of Boaventura in the first moment. Then he works with the analysis of the Legenda dos Três Companheiros (3S) written by Friars Leão, Rufino and Ângelo; Mirror of Perfection (SP) attributed to Frei Leão; the Legenda Perusina (LP), and the I Fioretti (Fior), in particular, the item entitled Le considerazioni sulle stimmate (Csd). We analyzed how the stigmatization of the saint was presented in hagiographic narratives, and we studied the writers' position on the topic. We identified differences in the description and importance given to stigmata in relation to ―official‖ hagiographic material, for example. In Le considerazioni sulle stimmate (Csd) the trajectory of the stigmata of Francis of Assisi is presented in a peculiar way, with episodes that differ from those contained in the ―official‖ Franciscan hagiographies. The work is extensive and recounts a journey that goes from the raising of Monte Alverne to the performance of miracles through the stigmata, something unprecedented in his itinerary. We also intend to highlight the mnemonic dispute of the miracle of the stigmata compiled from the perspective of companions close to Francis of Assisi, that is, those who make up the group ―nos qui cum eo fuimus‖. He presents a different interpretation of the official view of the hagiographic texts protected by the Church. What's more, the works reveal the importance of the performance of characters previously neglected in ―official‖ hagiographic material, such as Frei Leão.